Climate Change Disclosure in the Indonesian Banking Industry: a Case Study Of Jtrust Bank, Shinhan Bank, and Ok Bank (2020–2024) - Nurkhasanah, Nurkhasanah; Meiden, Carmel (Asian Journal of Social and Humanities, 2025)
Climate change has become a significant global issue and is increasingly gaining attention in the financial sector, including the banking industry. This study analyzes the level of climate change disclosure by three foreign banks in Indonesia JTrust Bank, Shinhan Bank, and OK Bank with a focus on the implementation of the Task Force on Climate-related Financial Disclosures (TCFD) framework, which covers four pillars: Governance, Strategy, Risk Management, and Metrics and Targets. Using a content analysis method of the Adequacy and Accuracy of Reporting indexes for the 2020–2024 period, both quantitative and qualitative assessments were conducted to evaluate the consistency and depth of disclosures. The results show that JTrust Bank has the highest level of disclosure, followed by Shinhan Bank and OK Bank. These differences are influenced by internal preparedness, strategic commitment to sustainability, and the regulatory policies of their home countries. This study emphasizes the importance of integrating climate issues into banks' governance and business strategies, and it is expected to provide both academic and practical contributions to encourage climate disclosure transparency in line with international standards